1997
DOI: 10.1007/s004150050083
|View full text |Cite
|
Sign up to set email alerts
|

Intra-observer reproducibility in measuring new putative MR markers of demyelination and axonal loss in multiple sclerosis: a comparison with conventional T2-weighted images

Abstract: New magnetic resonance (MR) measures considered to be putative workers of demyelination and axonal loss were found to be more closely related to clinical disability than T2-weighted MR imaging (MRI) findings in patients with multiple sclerosis (MS). In this study, we evaluated the reproducibility of such measurements in order to assess their reliability for longitudinal studies in MS. The intra-observer coefficients of variation for repeated measurements did not significantly differ among the MR techniques stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 23 publications
3
85
0
Order By: Relevance
“…In previous studies, 26,27 we found very low intraobserver variabilities when we measured all the MRI and MTI quantities mentioned above.…”
Section: Image Review and Quantificationmentioning
confidence: 58%
“…In previous studies, 26,27 we found very low intraobserver variabilities when we measured all the MRI and MTI quantities mentioned above.…”
Section: Image Review and Quantificationmentioning
confidence: 58%
“…26 Thalamic T2 hyperintense lesions were identified. Using T1-weighted images, we estimated baseline normalized brain volume by using SIENAX 27 software (www.fmrib.ox.ac.uk/fsl/ siena) and the percentage of brain volume change by using its longitudinal version.…”
Section: Image Review and Analysismentioning
confidence: 97%
“…In contrast to techniques based on regions of interest, this approach cannot provide any information concerning the regional pattern of tissue changes. However, the whole brain histogram analysis is highly reproducible 32,33 and provides easily comparable data for longitudinal studies without any image registration or subjective delineation of anatomic regions. In healthy subjects, Trace(D) histograms are characterized by a unimodal distribution with a narrow peak, indicating that most of the diffusion values measured in the cerebral volume are contained within a small range.…”
Section: Discussionmentioning
confidence: 99%